Surgical approach to pleomorphic adenomas arising in the palate: a 10-year retrospective study in a Brazilian population - Soares, Eduardo Costa Studart; Costa, Fábio Wildson Gurgel; Bezerra, Tácio Pinheiro; Nogueira, Carlos Bruno Pinheiro; Medeiros, José Rômulo de; Pita Neto, Ivo Cavalcante (Journal of Oral Diagnosis, 2016)
Salivary gland tumors represent an important group of neoplasms characterized by a great diversity of types and morphological variants. Pleomorphic adenoma is the most common benign tumor occurring in the major and minor salivary glands. The majority of case series described in the literature refers to epidemiological data of major and minor salivary gland tumors, generally being of a benign or malignant nature. Studies reporting exclusively surgical treatment experience with pleomorphic adenomas of the palate are scarce. Therefore, the aim of this study was to report data on the treatment experience with surgical removal of leomorphic adenoma of the palate together with to nearby mucosal lining with or without ostectomy. Clinical records of all patients diagnosed with pleomorphic adenoma of the palate seen at Brazilian public service dental clinic (Oral and Maxillofacial Surgery Division) and at a private clinic between March 1999 and November 2010 were reviewed. The analysis of the biopsied specimens yielded 10 cases during the 10-year period. Of all the patients 8 were women, with mean age 39 years. The most common main complaint was asymptomatic increase in volume (n = 9), with mean tumor size 2.1 cm. Most patients (n = 8) underwent excision of tumor and mucosal lining. One patient underwent bone ostectomy and in another, the tumor regressed after incisional biopsy.The mean follow-up was 26,8 months (12-42 months) with no recurrences, and the main complication was local discomfort and dysphonia (n = 2). In summary, surgical excision of the tumor and mucosal lining, with or without ostectomy, was shown to be an effective treatment modality for pleomorphic adenomas of the palate.